The Growth of Catfish (Clarias gariepinus) with aquaponic system - Ari Ridho; Usman M, Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in May 2013 at the Fish Hatchery and Breeding Laboratory Fisheries and Marine Science Faculty, Riau University. The aim of the research to know the productivity of catfish (Clarias gariepinus) with aquaponic system. The experimental methode with two treatments was applied in the research namely aquaponic and non-aquaponic. The result indicated that aquaponic have differential on growth of catfish (Clarias gariepinus). The best result was achieved by non-aquaponic. Total absolute body weight, absolute body length, daily growth rate, survival rate and productivity was 20,45 grams, 10,14 cm, 6,40 %/day, 78,89 %, and 7.421 grams respectively. Water quality during in the research with pH 6-7, disolved oxygen (DO) 1,78-4,7 mg/l, ammonia (NH3) 0,22-2,2 mg/l, nitrat (NO3-) 0,06-0,08 mg/l, nitrit (NO2-) 0,06-0,44 mg/l, temperature 30-310C.Keyword: Aquaponic, Survival rate, Clarias gariepinus